Botswana : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper for Botswana highlights the macroeconomic impact of an effectively implemented National Strategic Framework (NSF) program. The NSF is anchored on the goals of prevention, care, and support; management of the national response; economic impact mitigation; and provision of a strengthened legal and ethical environment. The treatment of the pandemic focuses on the administration of antiretroviral drugs to the infected, the effect of which would be to prolong their lifespan, as well as increase the average level of productivity.